Cloning, Localization and Expression Analysis of ZmHsf-like Gene in Zea mays - Hui-cong LI; Guo-liang LI; Zi-hui LIU; Hong-mei ZHANG; Yan-min ZHANG; Xiu-lin GUO (Journal of Integrative Agriculture, 2014)
Using homology cloning method, a heat shock transcription factor (Hsf) like gene, ZmHsf-like, was cloned from maize (Zea mays) leaves. Sequence analyses showed that the open reading frame (ORF) of the gene ZmHsf-like is 1 404 bp long, encoding 467 amino acids. The sequence of amino acids encoded by ZmHsf-like contains the most conserved and typical DNA-binding domain of Hsf family. By bombardment into onion epidermis, we firstly found that the ZmHsf-like was subcellular-located in nucleus. NucPred analysis revealed there is a classic NLS of KKRR peptide in protein. Real-time PCR showed that ZmHsf-like gene expressed in leaves, stems and roots of maize seedlings under normal growth conditions, and the highest expression level was in roots, lower in leaves and the lowest in stems. The ZmHsf-like gene expression could be up-regulated by heat shock, PEG, ABA, and H2O2 in different degrees, among which the heat shock and ABA worked more efficiently. Obvious differences of the peak value and its corresponding time point of ZmHsf-like gene expression were observed among treatments. Experiments with inhibitor further suggested that the up-regulation ZmHsf-like gene expression of heat shock was H2O2-dependent while the induction of ZmHsf-like with PEG did not depend on the existence of H2O2. These results pointed out that ZmHsf-like gene probably regulates responsive reactions to abiotic stresses especially heat shock and drought through different signal transduction pathways.